Strategies for change [soundrecording] - Martin, Allie Beth (Development digest premier series, 1974)
Individual and group presentations propose strategies to make public libraries relevant to society today. Innovations are suggested in such areas as library education, personnel management and outreach to urban and rural users. The importance of funding, technology and research to public libraries are also pointed out.